Croissance et répartition en présence d’investissements environnementaux non désirés - Laurent Cordonnier; Franck Van de Velde; Benoît Desmarchelier (Développement Durable et Territoires)
Sustainable development policies can have, inter alia incidences, that to impose on firms investments which otherwise they did not wish to undertake. We show that what is to be fear in the first place, with this type of “forced” investment, is not the decrease of the profitability of capital this is supposed to cause. For the (positive) effect of investment on the effective demand compensates for its (negative) cost effect. The fear is rather that of a significant rise of growth, because of the tension created by the new unproductive capital on production capacities. This rise of growth can be controlled if firms jump at the opportunity (tensions on the outputs) to increase their margins. In this most plausible scenario, an environmental policy passing by forced investments slightly stimulates growth, moderately decreases wage earners consumption in GDP (less than shareholders’), and improve employment.